COMMUNISM IN ЧЕБУРАШКА (ČEBURAŠKA) FILM: A SEMIOTIC STUDY - Kaprisma, Hendra (International Review of Humanities Studies, 2019)
This article discusses communism in the film titled Čeburaška by Eduard Uspenskij. The study aims to identify the ideology of communism in Čeburaška. The Roland Barthes' semiotic theory was used to analyse the film. In order to see communism contained in Čeburaška, the author used two stages of Roland Barthes' semiotic theory of denotation and connotation. The research used descriptive and criticism methods. In analysing communism in Čeburaška, the author also use the following concepts: the concept of character and characterization, ideology, and film as an ideology. The research result shows that Čeburaška contains elements of communism that can be seen from the signs in every scene. These signs include the red color that denoted the symbol of communism, the nature of cooperation (communal) found in the characters, and the animals in the zoo that were described as free from the capitalist. The publication background of the film also influences the presence of communism in Čeburaška.